Evidence for a Genetically Stable Strain of Campylobacter jejuni - Manning, G. (American Society for Microbiology, 2001)
The genetic stability of selected epidemiologically linked strains of Campylobacter jejuni during outbreak situations was investigated by using subtyping techniques. Strains isolated from geographically related chicken flock outbreaks in 1998 and from a human outbreak in 1981 were investigated. There was little similarity in the strains obtained from the different chicken flock outbreaks; however, the strains from each of three chicken outbreaks, including strains isolated from various environments, were identical as determined by fla typing, amplified fragment length polymorphism (AFLP) analysis, and pulsed-field gel electrophoresis, which confirmed the genetic stability of these strains during the short time courses of chicken flock outbreaks. The human outbreak samples were compared with strain 81116, which originated from the same outbreak but has since undergone innumerable laboratory passages. Two main AFLP profiles were recognized from this outbreak, which confirmed the serotyping results obtained at the time of the outbreak. The major type isolated from this outbreak (serotype P6:L6) was exemplified by strain 81116. Despite the long existence of strain 81116 as a laboratory strain, the AFLP profile of this strain was identical to the profiles of all the other historical P6:L6 strains from the outbreak, indicating that the genotype has remained stable for almost 20 years. Interestingly, the AFLP profiles of the P6:L6 group of strains from the human outbreak and the strains from one of the recent chicken outbreaks were also identical. This similarity suggests that some clones of C. jejuni remain genetically stable in completely different environments over long periods of time and considerable geographical distances.